MENGUASAI KEUANGAN RUMAH TANGGA DENGAN TEKNOLOGI: PELATIHAN LITERASI DIGITAL BAGI WARGA ‘AISYIYAH KECAMATAN CIBODAS KOTA TANGERANG - Rosyid, Rosyid; Mulatsih, Srie Nuning; Ratnasari, Aisyah (Community Services and Social Work Bulletin, 2023)
Financial managers using digital literacy in the family are still unfamiliar at this time. The lack of financial management in a family can trigger greater problems within it. However, when the family's finances are well planned and managed, then every member of the family will feel peace in his home. With the socialization of the use of digitalization on financial management for household mothers as well as technical guidance on using existing family financial management applications, the financial issues faced will be easier to anticipate in advance. If this problem can be solved by every family, then the purpose of a prosperous family can be realized. The dedication to the community is aimed at explaining the mastery of family financial management and providing technical guidance using Android-based financial management applications for household mothers. The post-test results showed that 79% of participants had a better understanding of how to use a family financial management app using a handheld phone device they had. This figure increased 41% of the pre-test result done before the activity was carried out.